Hepatic Radioembolization: A Multistep Theragnostic Procedure - Ramdhani, K; Lam, Marnix G E H; Braat, Arthur J A T; Smits, Maarten L J; El-Haddad, Ghassan (PET clinics, 2024)
This article provides a thorough overview of the practice and multistep approach of hepatic radioembolization. The current literature on hepatic radioembolization in primary or metastatic liver tumors as well as future perspectives are discussed.